Online shop sebagai sarana berbelanja masyarakat masa kini - Novelni Clara; Sabinus Beni (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
Online shop is an online shopping system where transactions that occur between sellers and buyers are entirely carried out online, this certainly gives a change to the shopping system in the era of technology, technological developments provide benefits to humans with innovations that occur, online shops emerge which become business fields and make it easier for the community when shopping for necessities. Currently, people are more dominant in shopping online becauseit is easier and more practical without consuming time, even the products needed are almost all available with various variations in each product or service. The online shop is currently growing because it has become a new shopping place besides a shopping center, apart from that the online shop is also the most visited site every day, even in a matter of seconds dozens of people can open an existing online shop line, operational time makes people happy to see products sold by online sellers, this has become one of the considerations for consumers to switch to shopping besides the availability of varied products and almost all of them are available which creates satisfaction for consumers and this is done almost every time making great interest in shopping online of course this becomes opportunities for online businesses, and become a business field and have reciprocity between sellers and buyers who both provide benefits for every need. The research objective of this research is to see how online shops can become shopping centers that are currently in demand by the community. This study uses a qualitative descriptive method to see why online shops are a means of shopping for today's society. Data was collected using the results of interviews with several people who are willing and are one of the people who like to shop online.Keywords: Online shop, Technology, Trend